Active teaching strategies for literacy learning in second-year students of Basic Education - Marroquin, Amparo; Aristega Sandoval, Yomaira Alejandra; Piñera Concepción, Yadyra de la Caridad; Martínez Isaac, Roger (Revista Minerva, 2025)
Learning to read and write is a fundamental pillar, not only in the academic field, but also for life in general. Therefore, the objective of this research was to design active teaching strategies for literacy learning in second-year elementary school students. A diagnosis was conducted using a mixed approach that incorporated theoretical and empirical methods such as classroom observation, teacher interviews, and a diagnostic test administered to 25 students. The results showed limited literacy proficiency, phonological difficulties, poor reading comprehension, low levels of written production, and teaching methods dominated by memorization and mechanical copying. In response, an organized proposal of active teaching strategies was designed, focusing on the cognitive, procedural, and attitudinal development of literacy skills, and integrating multisensory, playful, narrative, and phonological activities. The proposal included block planning, activity sequences, and instructional materials adapted to the educational level. It was validated through consultation with specialists, who evaluated the proposal as relevant, practical, and capable of immediate implementation in similar school settings. The proposal is aligned with the current Ecuadorian curriculum, improving reading comprehension, written expression, and students' motivation for literacy, thus contributing significantly to the goal of establishing a more efficient and comprehensive basic education.
Keywords: literacy; active teaching strategies; basic education; reading comprehension; writing